As tecnologias digitais da informação e comunicação no currículo da educação profissional técnica de nível médio - Amaral, Maria Lucia Soares do (2015)
This research falls within the context of research new technologies in education, graduate program in education: curriculum of the Pontifical Catholic University of São Paulo. The study aims to deepen the knowledge about the relationship between the role of digital information and communication technologies, public educational policies and the construction of the professional technical education curriculum. The main objective of this research is to analyze the national general curriculum guidelines of basic education, national high school curriculum guidelines, National curriculum guidelines of associate degrees and identify the references of use or integration of digital information and communication technologies to the development of the pedagogical project of technical courses in computer science course integrated into the high school. The methodology has descriptive qualitative approach, and as a method of research the case study. The theoretical referential about professional education issues; curriculum; digital information and communication technologies and is based on Gaudencio Frigotto, Marise Ramos, Michael Apple, Henry Giroux, Paulo Freire, Álvaro Vieira Pinto, Fernando José de Almeida, Maria Elizabeth Bianconcini de Almeida, among others. This research points to references about the use or integration of digital information and communication technologies in the national general curriculum guidelines of basic education, in national high school curriculum guidelines and national curriculum guidelines of associate degrees subsidize the construction of educational projects of technical courses in information technology integrated into the high school and are related to the use of didactic-pedagogic resource, such as curriculum content and competence, as a transversal element to the curriculum, technology as the basis for integrated curriculum curricular dimensions culture, science and technology as the transformation of science and knowledge, use of media such as educational resource, language and insertion to digital culture